Effect of Reaction Conditions on the Properties and Behavior of Wood Cellulose Nanocrystal Suspensions - Beck-Candanedo, Stephanie; Roman, Maren; Gray, Derek G (Biomacromolecules, 2005)
Sulfuric acid hydrolysis of native cellulose fibers produces stable suspensions of cellulose nanocrystals. Above a critical concentration, the suspensions spontaneously form an anisotropic chiral nematic liquid crystal phase. We have examined the effect of reaction time and acid-to-pulp ratio on nanocrystal and suspension properties for hydrolyzed black spruce acid sulfite pulp. Longer hydrolysis times produced shorter, less polydisperse black spruce cellulose nanocrystals and slightly increased the critical concentration for anisotropic phase formation. Increased acid-to-pulp ratio reduced the dimensions of the nanocrystals thus produced; the critical concentration was increased and the biphasic range became narrower. A suspension made from a bleached kraft eucalyptus pulp gave very similar properties to the softwood nanocrystal suspension when prepared under similar hydrolysis conditions.